Motivasi Orang Tua terhadap Pembentukan Moral Siswa - Afif, Shaleh (PT. Banjarese Pacific Indonesia, 2023)
This research is motivated by the low moral education of students. The moral formation of students depends on the people who shape them and their environmental situations. Madrasah is one of the Islamic educational institutions that can determine and shape students' personalities. In general, the aim of this research is to determine the reality of moral formation, the influence of parents' motivation for choosing Madrasah Ibtidaiyah on the moral formation of Class I MI MQ An-Nuur Sindangsari Kasomalang students, as well as the relationship between parents' motivation for choosing Madrasah Ibtidaiyah and the moral formation of Class I MI MQ An students. -Nuur Sindangsari Kasomalang. The method used in this research is a survey research method. Based on the results of data processing, it was found that the reality value reached 4.11 in the effective category. From the t test calculation, the sig value is obtained. 0.000 < 0.05, it can be concluded that there is an influence between parental motivation and the moral formation of Class I MI MQ An-Nuur Sindangsari Kasomalang students. From the results of correlation calculations, the value of sig.0.043 <0.05 is obtained, so it is concluded that there is a relationship between parental motivation and moral formation.